Senam Jantung Sehat Seri-I improves physical fitness, decreases the GDS scores and the level of NF-kB plasma elderly depression - Nita Fitria; L, Lynna; I, Shelly; L, Leonardo; P, Ambrosius (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Depression decreases the quality of life of the elderly. An exercise can help overcome this problem. Therefore, an exercise in the elderly is needed. Senam Jantung Sehat Seri-I (SJSS-I) was one of the proposed sport for the elderly. Oxidative stress that occurs in depressed elderly is characterised by an increase in plasma NF-kB levels. This research aimed to investigate the effects of SJSS-I in enhancing the physical fitness while decreasing the Geriatric Depression Scale (GDS)-15 score and plasma NF-kB level in the elderly. The experimental design was involved 30 elderly aged individuals with >60 years that further categorised into mild and moderate depression level, andthen completed the SJSS-I for 3 times a week for 12 weeks. Physical fitness was measured by the 6-minute test, GDS-15 score, and peripheral blood withdrawal done in pre- and post-workout. Plasma NF-kB level was measured by ELISA assay. A paired t-test and Wilcoxon test were used in statistical analysis. The results showed the physical fitness for mild levels was higher than moderate depression (35.273 + 8.86 m vs 264.40 + 118.18 m; p<0.001. Depressed GDS scores and NF-kB plasma levels were lower in mild depression group than moderate depression group (3.00 vs 7.00; p = 0.001 and 7.60 + 4.17 pg/ml vs 8.86 + 3.85 pg/ml; p<0.001). SJSS greatly imrpoved of the physical fitness with a decrease in GDS-15 scores and plasma NF-kB in the elderly with mildly depression than those with moderate level of depression.